An approach to cusqueñismo - Nieto Degregori, Luis (1994)
Cusqueñísimo is the word with which the feeling of deep identification of the people of Cusco with their city has been baptized. It is almost an axiom, in Cusco society, that this feeling translates into a desire, personal and collective, to work for the progress of Cusco, to return it to the place of importance it had in past times. Surely this is the reason why very little has been written about this feeling that is so present in the lives of the people of Cusco.